OPTIMIZATION OF SOLID STATE FERMENTATION CONDITIONS USING ARACHNIOTUSSPECIES FOR PRODUCTION OF FUNGAL TREATED WHEAT STRAW - F. Shahzad; M. Abdulah; A. S. Chaudhry; K. Javed; J. A. Bhatti; M. A. Jabbar; Z. Kamran; F. Ahmed; S. Ahmed; A. Ali; I. Irshad; N. Ahmad (Journal of Animal and Plant Sciences, 2016)
The study was carried out to determine the effects of optimum cultureconditions (substrate to water ratio, incubation period and salt concentrations, e.g. MgSO4.7H2O, CaCl2, KH2PO4 and urea) to increase the nutritive value of wheat straw (WS) by solid-state fermentation (SSF) with Arachniotus species. The performance of SSF product was evaluated in terms of favorable change in the crude protein (CP) contents of WS. Wheat straw based inoculum (seed culture) of Arachniotus sp. was prepared. WS (5gm) in 250 mL conical flask was mixed with a basal medium containing selected salts to attain the desired levels of water and nutrient concentration. A significant (p<0.001) increased CP contents was observed at 1:2 substrate water ratio at 4th day of incubation period.Maximum fungal protein contents in treated wheat strawwere found by addition of 0.05%, 0.075%, 0.15% and 0.15% ofMgSO4.7H2O, CaCl2, KH2PO4 and urea respectively. Itwas thus concluded that enhanced protein contents were achieved by incubation of wheat straw at 1:2 substrate water ratio with our selected salts concentrations during 4 days of incubation at 28°C.Hence,our findings highly support the use of above salts at our optimized concentrations for bioprocessing of wheat straw with Arachniotusspecies.
Keywords: Wheat straw; Salts concentrations; Fungi; Solid state fermentation; Arachniotus